Co-treatment With BGP-15 Exacerbates 5-Fluorouracil-Induced Gastrointestinal Dysfunction - McQuade, Rachel M.; Al Thaalibi, Maryam; Petersen, Aaron C.; Abalo, Raquel; Bornstein, Joel C.; Rybalka, Emma; Nurgali, Kulmira (Frontiers in Neuroscience, 2019)
Gastrointestinal (GI) side-effects of chemotherapy present a constant impediment to efficient and tolerable treatment of cancer. GI symptoms often lead to dose reduction, delays and cessation of treatment. Chemotherapy-induced nausea, bloating, vomiting, constipation and/or diarrhoea can persist up to 10 years post-treatment. We have previously reported that long-term 5-fluorouracil (5-FU) administration results in enteric neuronal loss, acute inflammation and intestinal dysfunction. In this study, we investigated whether the cytoprotectant, BGP-15, has a neuroprotective effect during 5-FU treatment. Balb/c mice received tri-weekly intraperitoneal 5-FU (23mg/kg/d) administration with and without BGP-15 (15mg/kg/d) for up to 14 days. Gastrointestinal transit was analysed via in vivo serial x-ray imaging prior to and following 3, 7 and 14 days of treatment. On day 14, colons were collected for assessment of ex vivo colonic motility, neuronal mitochondrial superoxide and cytochrome c levels as well as immunohistochemical analysis of myenteric neurons. BGP-15 did not inhibit 5-FU-induced neuronal loss, but significantly increased the number and proportion of choline acetyltransferase (ChAT)-immunoreactive (IR) and neuronal nitric oxide synthase (nNOS)-IR neurons in the myenteric plexus. BGP-15 co-administration significantly increased mitochondrial superoxide production, mitochondrial depolarisation and cytochrome c release in myenteric plexus and exacerbated 5-FU-induced colonic inflammation. BGP-15 exacerbated 5-FU-induced colonic dysmotility by reducing the number and proportion of colonic migrating motor complexes and increasing the number and proportion of fragmented contractions and increased faecal water content indicative of diarrhoea. Taken together, BGP-15 co-treatment aggravates 5-FU-induced gastrointestinal side-effects, in contrast with our previous findings that BGP-15 alleviates gastrointestinal side-effects of oxaliplatin.